Kepatuhan dalam membayar pajak Kendaraan bermotor di unit pelayanan pendapatan daerah Banjarmasin 1 dan 2 - Alfikri, Rahmatullah; Sarwani, Sarwani; Sayudi, Akhmad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aimed to examine and analyze the effect of Motor Vehicle Tax Relief Incentives, Service Quality, Taxpayer Knowledge of Taxes, Tax Sanctions, Taxpayer Awareness, Tax Administration System Modernization, and Income on Compliance in Paying Motor Vehicle Taxes at UPPD Banjarmasin 1 and 2. The Population of this study was Motor Vehicle Taxpayers registered in UPPD Banjarmasin 1 and 2. The determination of the number of total samples used the Ferdinand Formula as many as 340 Motor Vehicle Taxpayers with purposive sampling technique. This Study used primary data in the form of a questionnaire. The data quality testing used validity and reability tests. The data analysis technique used was multiple regression analysis. The model fit test used the F-test and the coefficient of determination (R2), the hypothesis testing used the T-test. The results of this study indicated that motor vehicle tax relief incentives, service quality, knowledge of taxpayes about taxation, modernization of the tax administration system, and income significantly affected compliance in paying motor vehicle taxes at UPPD Banjarmasin 1 and 2. In contrast, tax sanctions and tax payer awareness did not significantly affecr the compliance in paying Motor Vehicle Tax in UPPD Banjarmasin 1 and 2.